Quality of evidence supporting the role of probiotics for rheumatoid arthritis: an overview of systematic reviews - Li, Weiqing; Zhang, Yalan; Guo, Dandan; Gong, Rui; Yuan, Jiaxin; Yang, Huijun (Frontiers in Immunology, 2024)
Background: To evaluate the methodological quality, report quality, and evidence quality of metaanalysis (MA) and systematic review (SR) on the efficacy of probiotics in the treatment of rheumatoid arthritis (RA). Methods: Databases were used to identify eligible SRs/MAs until February 12, 2024. The methodological quality of the studies was assessed using AMSTAR-2 tool, the quality of the literature reports was scored using PRISMA checklists, and the quality of the evidence was graded using GRADE system. Results: Seven reviews including 21 outcomes were included. Methodological quality of the included reviews was of general low, and the entries with poor scores were 2, 4, and 7. By PRISMA checklists, there were some reporting deficiencies, and quality problems were mainly reflected in the reporting registration and protocol, comprehensive search strategy and additional analysis. GRADE results elevated the quality of evidence to be low or very low overall. Conclusions: Probiotics may have a therapeutic effect on RA, based on the evidence provided by the SRs/MAs in this overview. Nevertheless, there is still a lack of conclusive evidence due to methodological limitations in the included research. To make trustworthy judgments regarding the efficacy of probiotics in the treatment of RA, more large-scale, highquality randomized controlled trials are still required.